2018
DOI: 10.1007/s12035-018-1109-6
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of pGDNF DNA Nanoparticles Provides Neuroprotection in the Rat 6-Hydroxydopamine Model of Parkinson’s Disease

Abstract: Glial cell line-derived neurotrophic factor (GDNF) gene therapy could offer a disease-modifying treatment for Parkinson's disease (PD). Here, we report that plasmid DNA nanoparticles (NPs) encoding human GDNF administered intranasally to rats induce transgene expression in the brain and protect dopamine neurons in a model of PD. To first test whether intranasal administration could transfect cells in the brain, rats were sacrificed 1 week after intranasal pGDNF NPs or the naked plasmid. GDNF ELISA revealed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…The high concentration of GDNF within the SN protected DAergic neurons and dendritic fibers against the damage induced by 6-OHDA. In addition, the authors observed significant improvements in motor functions [250]. Therefore, these promising findings corroborate the important role played by GDNF to preserve DAergic neurons from cytotoxic triggers.…”
Section: Gdnf Therapysupporting
confidence: 65%
See 1 more Smart Citation
“…The high concentration of GDNF within the SN protected DAergic neurons and dendritic fibers against the damage induced by 6-OHDA. In addition, the authors observed significant improvements in motor functions [250]. Therefore, these promising findings corroborate the important role played by GDNF to preserve DAergic neurons from cytotoxic triggers.…”
Section: Gdnf Therapysupporting
confidence: 65%
“…Another strategy to increase GDNF levels in the inflamed brain has been developed in 2019 by Aly et al [250]. They induced brain cell transfection in vivo by delivering plasmid DNA (pDNA) encoding GDNF, either alone or mixed with a gelatine solution to form NPs, in a PD rat model.…”
Section: Gdnf Therapymentioning
confidence: 99%
“…As such, VEGF fosters the reorganization of the spinal motor network after SCI [71] and also underlies a protective effect against ischemia [69]. Among currently known neurotrophic factors, GDNF has the most pronounced neuroprotective effect, which is particularly relevant in ischemic brain damage [72,73] and neurodegenerative diseases [74][75][76]. The effects of GDNF on GluR2-containing α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors reduce the postsynaptic membrane permeability to calcium ions, which may be considered a possible mechanism for protecting neural cells from hypoxic damage [73].…”
Section: Secretome Compositionmentioning
confidence: 99%
“…For further exploration, some in vivo studies have been reported. Aly et al . chose to investigate GDNF gene therapy in a rat 6‐hydroxydopamine model of PD.…”
Section: Therapeutic Genes For Cns Diseasesmentioning
confidence: 99%
“…For further exploration, some in vivo studies have been reported. Aly et al 30 chose to investigate GDNF gene therapy in a rat 6-hydroxydopamine model of PD. PEGylated poly-L-lysine nanoparticles encapsulating GDNF gene were constructed and delivered to the CNS using a non-invasive route of administration, namely intranasal delivery.…”
Section: Many Previous Studies On Preclinical Models Of Pd and Clinicmentioning
confidence: 99%